2006
DOI: 10.1158/1541-7786.mcr-06-0095
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Gene Expression Predicts Sensitivity to Gefitinib in Non–Small Cell Lung Cancer Cell Lines

Abstract: Tyrosine kinase inhibitors

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 36 publications
11
114
0
Order By: Relevance
“…The nimotuzumab-resistant cell line H460 harbours a mutant form of KRAS (Balko et al, 2006) that has been associated with resistance to cetuximab (Lievre et al, 2006). However, we found that nimotuzumab also failed to inhibit EGF-induced EGFR phosphorylation and to enhance the cytotoxic effect of radiation in H1299 cells, which harbour wild-type KRAS (Coldren et al, 2006). These observations thus support the notion that a low level of EGFR expression at the cell surface is related to resistance to combined treatment with nimotuzumab and radiation, irrespective of KRAS status.…”
Section: Discussionmentioning
confidence: 57%
“…The nimotuzumab-resistant cell line H460 harbours a mutant form of KRAS (Balko et al, 2006) that has been associated with resistance to cetuximab (Lievre et al, 2006). However, we found that nimotuzumab also failed to inhibit EGF-induced EGFR phosphorylation and to enhance the cytotoxic effect of radiation in H1299 cells, which harbour wild-type KRAS (Coldren et al, 2006). These observations thus support the notion that a low level of EGFR expression at the cell surface is related to resistance to combined treatment with nimotuzumab and radiation, irrespective of KRAS status.…”
Section: Discussionmentioning
confidence: 57%
“…Second, the genes and proteins involved in primary resistance to EGFR-TKIs are not well defined. We undertook genomic and proteomic approaches to determine differentially expressed genes and proteins in the sensitive compared with the resistant cell lines from this study (32).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 3 public gene expression profile (GEP) microarray datasets: the GSE12276 dataset consisting of 204 primary breast cancer specimens from patients with metastatic disease (31); the GSE5851 dataset consisting of 80 colorectal cancer specimens taken from patients prior to treatment with cetuximab (39); and the GSE4342 dataset consisting of a panel of NSCLC cell lines analyzed for sensitivity to and resistance against gefitinib treatment (41). All datasets were retrieved from the Gene Expression Omnibus (GEO) database and processed using R scripting as previously described (65).…”
Section: Methodsmentioning
confidence: 99%
“…For the GSE4342 dataset, we analyzed the expression levels of PRL-3 in NSCLC cell lines (listed in Table 1 of the original publication; ref. 41) according to the references' designation of gefitinib-sensitive (IC50 ≤4.5 μmol/l, n = 15) or gefitinib-resistant (IC50 >4.5 μmol/l, n = 12).…”
Section: Methodsmentioning
confidence: 99%